Optimalisasi Kualitas Pembelajaran Pendidikan Agama Islam Melalui Partisipasi Siswa - Ahyar Rasyidi (PT Barkah Ilmi Fiddunya, 2024)
This study aims to explore the role of student participation in enhancing the quality of Islamic Religious Education at AL-Hidayah Islamic Elementary School in Banjarmasin. The research employs a qualitative method with a case study approach, utilizing interviews and observations to collect data from students, teachers, and the principal. The findings indicate that active student participation, both in class discussions, extracurricular activities, and group projects, significantly contributes to understanding and applying religious values. Furthermore, student involvement also enhances learning motivation and social interaction among peers. This study concludes that optimizing the quality of Islamic Religious Education can be achieved through strategies that encourage student participation, which in turn creates a more dynamic and meaningful learning environment. Recommendations are provided for the development of more interactive teaching methods that actively engage students in the learning process